The validity of the diabetes mellitus diagnosis in the Medical Birth Registry of Norway - Lars C. Stene; Ingvild Eidem; Siri Vangen; Geir Joner; Lorentz M. Irgens; Narve Moe (Norsk Epidemiologi, 2007)
The Medical Birth Registry of Norway (MBRN) has registered all births in Norway since 1967 and diabetes is registered as a maternal diagnosis. We present original data assessing the validity of the diabetes diagnosis. Among women with known pre-gestational type 1 diabetes, 97% of births during 1976-1998 (old registration form) were identified as pre-gestational diabetes in the MBRN. For births 1999-2004 (new registration form), 94% were identified as pre-gestational diabetes in the MBRN. Of cases coded as pre-gestational diabetes by the MBRN, 80% were confirmed by the medical record for births during 1998, while more than half of the births incorrectly coded as pre-gestational diabetes really were gestational diabetes. Among births coded as gestational diabetes, 89% were confirmed in the medical record. In conclusion, the sensitivity of the pregestational diabetes diagnosis in the Medical Birth Registry of Norway was very good, particularly in the earlier period, but the information in the MBRN on births before 1999 was not sufficient to classify pregestational diabetes as type 1 – or type 2 diabetes. The type of diabetes can be specified for births from 1999 onwards, but the predictive values are unknown. The predictive value for pre-gestational diabetes in 1998 was less than optimal but acceptable for a routine registry not specialised for diabetes